THE EFFECT OF USING PICTIONARY GAMES ON STUDENTS’ VOCABULARY MASTERY - Yelvia, Erli (Universitas Mahaputra Muhammad Yamin, 2023)
This research was conducted since most of the students still had problems in learning English, especially in vocabulary mastery. Most of the students had difficulties mastering vocabulary, lack of practice in English and students were not motivated to study English. Thus, this research aimed at finding out the effect of using Pictionary Game on students’ Vocabulary Mastery in seventh grade in SMPN 2 Bukittinggi. A quasi-experimental design was used in this study. This study employed two classes: experimental and control. The population was drawn from SMPN 2 Bukittinggi seventh-grade students. In this study, the sample was 28 students from the control group and 31 students from the experimental group. To analyze the data collection procedure, a t-test formula was used. According to the results for the experiment class's pre-test and post-test scores, the t-obtained (12,92) was greater than the t-table (2,042) with the degree of freedom (df) 30 and (0,025). The t- obtained in the calculation of the post-test for both classes was (2,011), which was higher than the t-table (1,672) with (df) 57 and =0,05. So, it can be concluded that the entire hypothesis were accepted. It has been indicated that using a Pictionary game can assist students in improving their vocabulary mastery.